Pengaruh Struktur Modal, Beban Bunga dan Beban Pajak Terhadap Kinerja Perusahaan: Studi Kasus Pada Perusahan Sektor Otomotif dan Komponennya yang Tercatat di Bursa Efek Indonesia, 2009-2015 - Ayu Puspitaningtyas, SE., MM. (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2018)
The purpose of this study was to analyze the impact of capital structure, interest expense and tax on financial performance of automotive and components sector companies listed in Indonesia Stock Exchange (IDX). This study employed the descriptive and regression analysis of panel data. This study covered annual data of 12 automotive and components sector companies listed in the BEI at year 2009-2015. Datas were analysed using multiple regression. The study conclude that capital structure which represent by Debt to Equity Ratio (DER), Interest Expense, and Tax Expense have simultaneously and significant effect towards profitability which represent by Return On Equity (ROE). Only Interest Expense have partial and significant effect toward probability which represent by Return On Equity (ROE). Based on the result, researcher obtained two crucial implications, first is for automotive company have to be considered by management to monitor the company solvability, because high level of solvability indicates that company have so many capability to payment interest and loan. The second is suggestion for the investor (have been or will be) is that they should, not only, considering financial fundamental aspects of company, but also have to consider the external aspect that can influence company’s return on equity.